PEMAKNAAN DAN IMPLEMENTASI PRINSIP EX AEQUO ET BONO DALAM PENYELESAIAN SENGKETA EKONOMI SYARIAH MELALUI BASYARNAS - Umam, Khotibul; Nasution, Muhammad Guntur Hamonangan Nasution (Faculty of Law, Parahyangan Catholic University, 2023)
The dispute resolution mechanism in BASYARNAS, an Islamic economics arbitration institution, is based on the principle of ex aequo et bonowhich still raises questions regarding its interpretation and implementation. This research aims to comprehend the meaning, limitations, and implementation of the ex aequo et bono principle in the decisions of BASYARNAS. This study uses a normative legal research method with statutory, conceptual, and case study approaches. The findings show that the interpretation of the ex aequo et bono principle correlates with Sharia principles in terms of rules and principles, prohibition of ultra petita, and arbitrator's capability. Meanwhile, the limitations of the application of ex aequo et bono are closely related to the consensual principle of the parties, primary petitum demands, Sharia principles, pacta sunt servanda, and the principle of good faith. These concepts will be taken into account in reviewing the nullity of a contract and its consequences thereafteer. In addition, the implementation, as seen in the Decision of BASYARNAS Case No. 01/Year 2010/BASYARNAS, shows that fair and propriety assessment of the panel does not solely arise from the phrase ex aequo et bono. The decision also negates the elements of the agreement and the good faith of the parties as a basis for continuing an existing contract.